Motherhood and meaning in Medieval sculpture : representations from France, c.1100-1500 - Bleeke, Marian (Boydell studies in medieval art and architecture, 2017)
What can medieval sculptural representations of women tell us about medieval women's experiences of motherhood? Presumably the work of male sculptors, working for clerical patrons, these sculptures are unlikely to have been shaped by women's maternal experiences during their production. Once produced, however, their beholders would have included women who were mothers and potential mothers, thus opening a space between the sculptures' intended meanings and other meanings liable to be produced by these women as they brought their own interests and concerns to these works of art. Building on theories of reception and response, this book focuses on interactions between women as beholders and a range of sculptures made in France in the twelfth through sixteenth centuries, aiming to provide insight into women's experiences of motherhood; particular sculptures considered include the Annunciation and Visitation from Reims cathedral, the femme-aux-serpents from Moissac, the transi of Jeanne de Bourbon-Vendome, the Eve from Autun, and a number of French Gothic Virgin and Child sculptures.